Morphology and distribution of a deep-water Narcomedusa (Solmarisidae) from the northeast Pacific - Mary Needler Arai; Michael J. Cavey; Beverley A. Moore (Scientia Marina, 2000)
Specimens of Solmaris sp. (Solmarisidae, Narcomedusae) with only four tentacles were collected in the northeast Pacific. The majority were collected in Canadian Pacific waters by Tucker trawl from stations outside the 500-m contour off the west coast of Vancouver Island, British Columbia, at depths of 300-700 m. Six were collected in vertical hauls at Station P (50oN, 145oW). The oral stomach wall contains three prominent rings of tissue. There is a peripheral ring of aggregates of gonadal tissue. Nematogenic areas with three types of nematocysts form an intermediate ring closer to the mouth than the gonads, and they also overlie the gonadal position where nematogenic tissue extends out to the base of each tentacle. Immediately surrounding the mouth, the epithelium of the oral stomach wall is greatly thickened, and this central ring contains large numbers of secretory cells.